Sistem Informasi Administrasi Multi Cabang UD Bangun Persada - Anggita Christina; Yulia Yulia; Anita Nathania (Jurnal Infra, 2019)
UD Bangun Persada is a trading business that sells various building materials and tools which were established in 1998. UD Bangun Persada is located in the city of Surabaya. Currently UD Bangun Persada has 2 main stores and 3 branches with 32 employees. At present, to manage its business processes UD Bangun Persada is still running manually. Every transaction that occurs must be recorded in the ledger and check the stock of each store entirely also manually This is felt to be less effective because of the length of the process to find out the latest stock number of each store and the absence of reports that can explain the development of each store as a whole.Based on the existing problems, then in this thesis a multi-branch administrative information system is created that can be connected to each other or store. So that every sale, purchase, stock inventory, return, debt and receivables transaction can be managed in a structured manner and can produce reports needed to explain the development of UD Bangun Persada. This Administration Information System will be based on websites with PHP 7 based programming languages, assisted with Bootstrap and JQuery libraries and using MySQL databases.Based on the results of this thesis research, it can be concluded that overall the administrative information system has fulfilled the needs of UD Bangun Persada, especially in the stock management function so that the stock of each store can be known in real time. but in its application it can be further developed especially for accounting calculations and in helping to make decisions through available data.